Representations of Transnational Human Trafficking Present-day News Media, True Crime, and Fiction (Springer International Publishing, 2018)
This open access edited collection examines representations of human trafficking in media ranging from British and Serbian newspapers, British and Scandinavian crime novels, and a documentary series, and questions the extent to which these portrayals reflect the realities of trafficking. It tackles the problematic tendency to under-report particular types of victim and forms of trafficking, and seeks to explore both dominant and marginalised points of view. The authors take a cross-disciplinary approach, utilising analytical tools from across the humanities and social sciences, including linguistics, literary and media studies, and cultural criminology. It will appeal to students, academics and policy-makers with an interest in human trafficking and its depiction in the modern day.